2019
DOI: 10.1038/s41416-019-0413-x
|View full text |Cite
|
Sign up to set email alerts
|

High filamin-C expression predicts enhanced invasiveness and poor outcome in glioblastoma multiforme

Abstract: Background Glioblastoma multiforme (GBM), the most common brain malignancy in adults, is generally aggressive and incurable, even with multiple treatment modalities and agents. Filamins (FLNs) are a group of actin-binding proteins that regulate the actin cytoskeleton in cells. However, the role of FLNs in malignancies—particularly in GBM—is unclear. Methods The relation between FLNC expression and overall survival in GBM was evaluated by the Kaplan−Meier analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
(55 reference statements)
0
23
0
Order By: Relevance
“…FLNs are involved in various signaling pathways; thus, a relationship between FLNs and tumor progression has been suggested [11], with evidence regarding the roles of FLNA and FLNB in cancer having been reported [22,23]. Although there are only a few reports showing the relationship between FLNC and tumor [11,12,14,19,21], the presence of multiorgan tumors in this case implies the possible relationship of FLNC mutation with tumorigenesis. Although accumulation of clinical data and future research is required to clarify the relationship, we should pay attention to the presence of tumors in the medical management of patients with FLNC myopathy.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…FLNs are involved in various signaling pathways; thus, a relationship between FLNs and tumor progression has been suggested [11], with evidence regarding the roles of FLNA and FLNB in cancer having been reported [22,23]. Although there are only a few reports showing the relationship between FLNC and tumor [11,12,14,19,21], the presence of multiorgan tumors in this case implies the possible relationship of FLNC mutation with tumorigenesis. Although accumulation of clinical data and future research is required to clarify the relationship, we should pay attention to the presence of tumors in the medical management of patients with FLNC myopathy.…”
Section: Discussionmentioning
confidence: 78%
“…The most notable finding in this case was the comorbidity of multiorgan tumors (urinary bladder and breast cancer) and a polyp (gastric fundic polyp). Recently, several reports have suggested an association between the dysregulation of FLNC and various tumors, such as prostate cancer [18,19], ovarian cancer [20], gastric cancer [12], urinary bladder [21], breast cancer [13], and glioblastoma [14]. One study reported that the variants of FLNC were found in 4% of invasive lobular breast cancers associated with CDH1 mutations [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 FLNA is an actin-binding protein involved in cell motility and invasion of glioblastoma cells, 14 and its overexpression is associated with progression to metastasis and/or poor prognosis in several cancers. 15 Its effect could be synergistic with the mutation of the formin FHOD1, also involved in migration of glioma cells in vitro . 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Although Filamin has been originally identified as a tumor promoting factor, prognostic value is mainly dependent on its subcellular localization and binding with different proteins [ 205 ]. High Filamin levels have been shown to be predictors of poor patient outcome in several tumors including melanoma, breast, and glioblastoma multiforme [ 206 ]. Whereas, the Filamin A isoform has been shown to inhibit tumor progression by regulating breast cancer type 1 susceptibility protein (BRCA1) expression in human breast cancer [ 207 ].…”
Section: Actin-related Regulatory Functions That Control Tgfβ Signmentioning
confidence: 99%